PERBANDINGAN NILAI C-REACTIVE PROTEIN METODE aglutinasi Lateks DAN METODE FLUORESCENCE IMMUNOASSAY (FIA) PADA PASIEN PRA SECTIO - Nurhidayanti Nurhidayanti (IKesT Muhammadiyah Palembang, 2023)
Introduction: Examination of C-Reactive Protein (CRP) levels in the blood is a marker of the acute phase in humans which is useful for the diagnosis and monitoring of inflammatory diseases. The Latex Agglutination method is often used to obtain quick and simple results as a screening test for elevated CRP levels. Currently, a quantitative CRP examination is available in order to measure CRP levels more quickly. Fluorescene Immunoassay (FIA) is a method that has improved sensitivity and precision so that it can detect low CRP concentrations. This study aims to determine differences in C-Reactive Protein (CRP) values of the Latex Agglutination method and the FIA method in patients at Bunda Palembang Hospital in 2023. Method: Cross Sectional. The research was conducted in January 2023 at Bunda Palembang Hospital with a total sample of 38 samples. Results: The average value of C-Reactive Protein using the Latex Agglutination method was 6.6 mg/L and the FIA method was 7.0 mg/L. Data analysis of the Latex Agglutination method showed that there were differences between the FIA method and Asymp. Sig. (2-tailed) is 0.029. The sensitivity and specificity were 73.91% and 100% for the Latex Agglutination method, and 100% and 71.43% for the FIA method, respectively. Conclusion: There are differences in the C-Reactive Protein Value examination by the Latex Agglutination Method and the Fluorescene Immunoassay (FIA) Method..